'Graphic Details'. Issue 2 (1st December 2015) - Stewart, Keara
I was invited to visually document and respond to the 'Graphic Details Symposium' at JW3. Through my association with Laydeez do Comics, who had an evening slot at the symposium, I felt an intimate and personal connection to the subject matter and speakers. For this work, my process involved live drawing of the speakers and their slides. Also included are responses to the illustrative works associated with the event, the exhibition newspaper/catalogue and 'Graphic Details' text, edited by Sarah Lightman. For me, drawing them allows me to absorb a different aspect of the work. The themes that resonated with me from the symposium were those of memory and vulnerability. Responding to these themes through the fragility and immediacy of live drawing, and the nostalgia and immediacy of Polaroid photographs ties in with my drawing style of capturing a moment.